The Japanese Novel of the Meiji Period and the Ideal of Individualism - Walker, Janet A., 1942- (Book collections on Project MUSE., 2019)
The Western ideal of individualism had a pervasive influence on the culture of the Meiji period in Japan (1868-1912). Janet Walker argues that this ideal also had an important influence on the development of the modern Japanese novel. Focusing on the work of four late Meiji writers, she analyzes their contribution to the development of a type of novel whose aim was the depiction of the modern Japanese individual. Professor Walker suggests that Meiji novels of the individual provided their readers with mirrors in which to confront their new-found sense of individuality. Her treatment of these novels as confessions allows her to discuss the development of modern Japanese literature and "the modern literary self" both in themselves and as they compare their prototypes and analogues in European literature. The author begins by examining the evolution of a literary concept of the inner self in Futabatei Shimei's novel Ukigumo (The Floating Clouds), Kitamura Tokoku's essays on the inner life, and Tayama Katai's I-novel Futon (The Quilt). She devotes the second half of her book to Shimazaki Toson, the Meiji novelist who was most influenced by the ideal of individualism. Here she traces Toson's development of a personal ideal of selfhood and analyzes in detail two examples of the lengthy confessional novel form that he created as a vehicle for its expression. Janet A. Walker is Associate Professor of Comparative Literature at Livingston College, Rutgers University. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905